Angka Kelangsungan Iiidup (Survival Rate) Penderita kanker payudara yang dirawat di RSUP Dr. Sardjito Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
ABSTRAk The cancer survival rate study in Indonesia is very difficult to be carried out. It is due the lack of patients awareness for medical control after their treatment. this paper deal with the possibility of follow up study of breast cancer patients. Breast cancer patients admited to the Sardjito Hospital for treatment during the year of 1985 through 1986 who are Yogyakarta Special Region inhabitant were used as the case. Follow up study were carried out if patients visited the hospital control or by using postcard wheather patients were in a good condition. The time from the first time disgnosis up to the end of the follow up study were recorded as survival time. Descriptive methode were utilized as the analysis. The result recorded that the 3 year survival rate of breast cancer patients stage II was 27%, stage III 16%, It is suggested that postcard follow up study could be utilized as a method for survival study.